Spirited away - Chase, Daveigh; Pleshette, Suzanne, 1937-2008.; Marsden, Jason, 1975-; Egan, Susan, 1970-; Holly, Lauren; Stiers, David Ogden; Chiklis, Michael, 1963-; Strong, Tara, 1973-; Ratzenberger, John.; 1969-; 1962-; Kagawa, Megumi; et al. (Burbank, Calif. : Walt Disney Home Entertainment : Buena vista Home Entertainment, distributor, 2001)
When a young girl gets trapped in a strange new world of spirits, she must call upon the courage she never knew she had to free herself and rescue her parents.
Disc 1. Feature presentation ; The art of Spirited away. -- Disc 2. Behind the microphone ; Select storyboard-to-scene comparison ; The Nippon television special ; Original Japanese trailers.
A DVD release of the motion picture originally produced in 2001.
Special features: special introduction by John Lasseter; the art of "Spirited away"; The Nippon Television special; select storyboard-to-scene comparison; voice talent featurette; original Japanese trailers.
English language voices: Daveigh Chase, Suzanne Pleshette, Jason Marsden, Susan Egan, David Ogden Stiers, Lauren Holly, Michael Chiklis, John Ratzenberger, Tara Strong.
MPAA rating: PG; for scary moments.
DVD; NTSC. Region 1; Dolby Digital 5.1 surround; widescreen (2.0:1).
In English with optional French, Japanese and Spanish soundtracks; closed--captioned.
Keywords: Spirits -- Juvenile drama; Parent and child -- Juvenile drama; Motion pictures, Japanese; Spanish language -- Films; French language -- Films; Japanese language -- Films; French DVDs 2003.; Japanese DVDs 2003.; French language; Japanese language; Motion pictures, Japanese; Parent and child; Spanish language; Spirits; Animated films; Children's films; Drama; Fantasy films; Juvenile works; Motion pictures; Animated films; Fantasy films; Children's films